G248(P) Significant findings? difficulties triaging referrals of children with heart murmurs. (12th March 2018) - Round, J; Cartwright, E
Abstract : Aims: Typical primary care practice is to refer all children with persistent heart murmurs for further assessment. Although most of these murmurs are benign, those with serious underlying pathology are at risk of having their care delayed because of the number of patients referred. This practise may also lead to unnecessary anxiety for parents and patients. We sought to analyse GP referral letters to establish if patients at risk of structural disease could be identified to enable them to be seen sooner. Method: GP referral letters to a tertiary hospital paediatric cardiology clinic requesting evaluation of a murmur of a tertiary hospital in the period from January 2016 to May 2017 (n=90) were identified. They were analysed for features suggestive of significance of the murmur. These were then compared to the echocardiography findings in the subsequent clinic letter. Results: Of the letters analysed, 10% of patients had underlying structural abnormalities. 5/90 referrals (5.5%) specified a grade of murmur, and 31/90 (34%) specified a location of the murmur. 23/90 (25.5%) referrals mentioned the presence or absence of associated features. No characteristics of the murmur were associated with the presence of a structural cause. Conclusion: This study demonstrates that it is currently impossible to prioritise patients based on information provided in GP referral letters. This suggests either provision of cardiology screening outpatient clinics should be increased, or more attention paid to learning about children's heart disease in undergraduate and GP curricula. Referral using a specific form may also prompt referrers to seek specific findings and improve triage.